(untitled) (American Journal of Technology and Applied Sciences, 2023)
Investigate the hole transfer mechanism in a-Si:H films using photovoltage characteristics (photo-CVCH) of a vidicon target. Theoretically obtained, if the concentration of photogenerated injected holes exceeds the concentration of defective states, then in the a-Si: H mobility gap in photo-CVCH, a portion is observed that obeys the quadratic law (I U2). It was explained that in order to obtain reliable information from this section on the hole transport mechanism, it is necessary to take into account changes in the a-Si: H dielectric constant and hole lifetime depending on the applied voltage.